The Trinity : On the Nature and Mystery of the One God - White, Thomas Joseph, 1971- (Book collections on Project MUSE., 2022)
"This book explores the mystery of Trinitarian monotheism; engages with modern theologians on major topics such as Trinitarian creation, Incarnation, and crucifixion; illustrates how the human life, death, and resurrection of Jesus reveal the inner life of God as Trinity"--